INSIGHT INTO TRAINING NEEDS OF GOVERNMENT VETERINARY OFFICERS FROM SUB-TROPICAL REGION OF INDIA - Pragya Joshi; Rupasi Tiwari; Sushant Handage; Pratikshya Panda; Triveni Dutt (Journal of Animal and Plant Sciences, 2023)
The present study aimed at identifying the training needs of the veterinary officers serving under different state governments. Three states of the sub-tropical region of the country namely Uttar Pradesh, Uttarakhand, and Jammu and Kashmir were chosen purposively for their accessibility and ease in communication. A total of 120 veterinary officers were selected i.e., 40 from each state. A Schedule was developed that consisted of 44 statements across different domains viz clinical care, diagnostics, managemental practices, extension activities. The responses were recorded by assigning scores as 3, 2 & 1 for most needed, needed and least needed respectively. The results revealed that most of the training needs were associated with management of infertility and reproductive health in livestock (Mean Obtained Score: MOS 2.57), followed by sample collection, storage, and transportation procedure in disease diagnosis (MOS 2.57) and disease diagnosis through ultrasonography and radiography (MOS 2.56). Under the specific domains viz. clinical care, diagnostics, managemental practices, extension related activities, training needs were concentrated in the domains of management of infertility and reproductive health in dairy cows and buffaloes (MOS 2.57), sample collection, storage and transportation for disease diagnosis (MOS 2.57), handling the outbreaks ( MOS 2.43), technical and popular writing skills (MOS 2.39), stress and time management (MOS 2.45), and biosafety measures (MOS 2.34) respectively. To meet the training needs the study suggests organizing formal and informal trainings and creating better training resources in the reported niche areas. Focusing on improving the training experience can help in augmenting the skills of veterinarians, which indirectly helps to realize the objective of empowering the animal husbandry sector.
Keywords: Clinical care; Diagnostic; Management; Training needs and Extension